Effect of a newly developed ready-to-use supplementary food on growth indicators in children with mild to moderate malnutrition. (August 2020) - Azimi, F.; Esmaillzadeh, A.; Alipoor, E.; Moslemi, M.; Yaseri, M.; Hosseinzadeh-Attar, M.J.
Abstract: Objectives: Malnutrition is one of the leading causes of death among children younger than five years. In this study, we aimed to formulate a ready-to-use supplementary food (RUSF), based on local food products, and investigate its efficacy on growth indicators in children with mild to moderate malnutrition. Study design: This is a randomized controlled clinical trial. Methods: This study was performed in six health centers in Shahr-e-Rey, Tehran, Iran, between April and October 2017. One hundred children, aged 24–59 months, with mild to moderate malnutrition (weight-for-height Z-score [WHZ] between −3 and −1) were randomly assigned to two groups to receive either 1–3 sachets of RUSF or normal diet for 8 weeks. All mothers and caregivers received nutrition education. Growth indicators including weight and height, WHZ, and body mass index (BMI), along with clinical outcomes, were assessed. Results: Children who received RUSF had a significant increase in weight (1.44 ± 0.38 vs 0.7 ± 0.32 kg, respectively, P < 0.001), and BMI (1.2 ± 0.47 vs 0.35 ± 0.33 kg/m 2, respectively, P < 0.001) compared with the control group. There was a greater daily weight gain during the first 4 weeks ( P < 0.001) and throughout the study ( P = 0.013) in the RUSF group. Daily height gain was considerably higher in the RUSF group during the first 4 weeks ( P = 0.027). Children in the RUSF group had more improvement in WHZ (1.18 ± 0.41 vs 0.41 ± 0.31, P < 0.001) after supplementation. Besides, 92% of the RUSF and 12% of the control group reached to WHZ > −1 at the end of the study ( P < 0.001). There was lower prevalence of diarrhea (12% vs 28.6%, respectively, P = 0.01) and marginally lower fever (16% vs 36.7%, respectively, P = 0.05) in the intervention than in the control group. Conclusions: A newly developed RUSF improved growth indicators and clinical outcomes in children with mild to moderate malnutrition. Clinical Trial Registry number: IRCT2017021315536N6 (registered at www.irct.ir ) Highlights: Children in the ready-to-use supplementary food (RUSF) group had significant increase in weight, height, body mass index, and weight-for-height Z-score (WHZ) and were more likely to reach a WHZ >-1 (not malnourished) than those in the control group. Children in the RUSF group had lower prevalence of diarrhea and a marginally lower fever rate.